High prevalence of Helicobacter pylori infection in cohabiting children. Epidemiology of a cluster, with special emphasis on molecular typing. Issue 3 (March 1994) - Vincent, P; Gottrand, F; Pernes, P; Husson, M O; Lecomte-Houcke, M; Turck, D; Leclerc, H
Abstract : Intrafamilial cases of infection with the same strain of Helicobacter pylori (H pylori) have been reported but these clusters were too small to distinguish between person to person spread or coinfection from a common environmental source. To gain more information on the mode of transmission of H pylori, an epidemiological survey with bacterial strain differentiation by restriction endonuclease analysis of chromosomal DNA was carried out in an institution of 117 children with encephalopathy (aged 3.5 to 19 years). All children with antibodies against H pylori had gastroscopy to obtain gastric biopsy specimens. The prevalence of infection (confirmed histologically or microbiologically, or both) was 38% (45/117), and rose to 67% in one of the five sections of the institution. H pylori was isolated in 34/45 cases, and 22 different strains were found of which five strains were present in more than one child. Up to seven children were infected by the same strain, five of them were living in the same section. Analysis of the characteristics of infected children showed the predominant role of living conditions and the period of time cohabiting in this unexpectedly high prevalence of H pylori infection in children living in good sanitary conditions.